STRUKTUR KOMUNITAS FITOPLANKTON PADA PERAIRAN MAYANGAN PROBOLINGGO, JAWA TIMUR - Sartimbul, Aida; Ginting, Felixtha Robertus; Pratiwi, Dwi Candra; Rohadi, Erfan; Muslihah, Nurul; Aliviyanti, Dian (JFMR (Journal of Fisheries and Marine Research), 2021)
The waters of Mayangan, Probolinggo are waters that have ports with the status of the Coastal Fisheries Port (PPP). The existence of PPP Mayangan, Probolinggo can negatively influence the quality of the water in these waters. Phytoplankton as a primary producer in a waters very much depends on water quality fluctuations that occur in aquatic ecosystems. The role of phytoplankton as a bioindicator gives an idea of the condition of the water quality contained in a waters. This study aims to determine the structure of the phytoplankton community as a bioindicator of water quality in the waters of Mayangan, Probolinggo. Phytoplankton sampling and water quality were conducted in situ. Depth of data was obtained through the National Batimetri website, Geospatial Information Agency (BATNAS BIG). Phytoplankton samples were taken by horizontal method, water quality samples were also taken by repetition 3 times. Data analysis using Pearson Correlation analysis with the help of SPSS 16.0 application. The results showed the average value of air quality in the waters of Mayangan, Probolinggo was 36.76 Â° C, pH 7.19, salinity 33.5 ppt, brightness 6.48 m, nitrate 0.023 mg / l, phosphate 0.022 mg / l , and a depth of 5.26 m. The most commonly found phytoplankton are Chaetoceros and Skeletonema in which both genera are included in Harmful Alga Bloom (HAB). Based on the correlation analysis test, water transparancy was positively correlated with the abundance of phytoplankton in the waters of Mayangan, Probolinggo.Â